Whose intergenerational mobility? A new set of estimates for Indonesia by gender, geography, and generation - Diding Sakri; Andrew Sumner; Arief Anshory Yusuf (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Various scholars have estimated levels of intergenerational mobility in OECD countries. Fewer estimates are available for developing countries, where mobility arguably matters more due to starker differences in living standards. This paper presents new estimates of mobility for a developing country, namely Indonesia. The estimates are based on data from five waves of the Indonesian Family Life Survey, a longitudinal analysis of socio-economic status which began in 1993. We constructed a pooling sample consisting of 9,445 matching pairs of children and their parents. The paper estimates relative mobility using the intergenerational elasticity of income. We find that although, overall, the intergenerational elasticity of income is low compared with other developing countries, the level of mobility in Indonesia differs markedly by children's gender and across provinces and generations.
Keywords: D63; J62; 330; intergenerational mobility; longitudinal analysis; Indonesia; Indonesian Family Life Survey